Efficacy of polyherbal formulations for prevention of COVID‐19 infection in high‐risk subjects: A randomized open‐label controlled clinical trial. (5th July 2022) - Chandra, Kailash; Das, Ayan Kumar; Banday, Sumeera; Rana, Naushad Ali; Arora, Mohini; Jain, Sonal; Islam, Farzana; Agarwal, Shashank; Kashyap, Varun; Joshi, Santosh; Mueed, Asad; Dudeja, Mridu
Abstract: COVID‐19 is arguably the biggest health crisis the world has faced in the 21st century. Therefore, two of the polyherbal formulations, Infuza and Kulzam were assessed for the prevention of COVID‐19 infection as a repurposed medication. Four hundred seven high‐risk subjects were recruited in the present open‐label randomized controlled clinical trial for eligibility. After assessment for eligibility, remaining 251 subjects were randomized to the test and control groups. Further, 52 high‐risk subjects in Infuza, 51 in Kulzam, 51 in Infuza & Kulzam and 53 in control group completed the 14 days of intervention/assessment. The phenotyping of lymphocytes at baseline (0 day) and after 14 days of treatment was carried out by flow cytometry assays. A total of 15.09% high‐risk subjects in control group turned positive as compared to only 7.69% in Infuza, 3.92% in Kulzam and 1.96% in Infuza & Kulzam groups. The rate of conversion to COVID‐19 infection in Infuza & Kulzam group was minimal and statistically significant as compared to control group (p0.017). No significant changes in phenotype of lymphocytes (T, B, NK cells), absolute lymphocyte count and cytokine levels were found in study groups. However, there was a decreasing trend of hs‐CRP level in high‐risk subjects after intervention of polyherbal formulations for 14 days. The combination of Infuza and Kulzam may synergistically prevent COVID‐19 infection in high‐risk subjects of COVID‐19.